How Can Schizophrenia Occur? Case Study of Life Journey of Schizophrenic Survivor - Wafa, Sirril; Cahyanti, Ika Yuniar (Psikostudia : Jurnal Psikologi, 2023)
Schizophrenia a psychosis problem with the number sufferers in Indonesia touching 2 million people, the number cases is not comparable with public knowledge regarding the causes of schizophrenia. The research objective is to present a description of the causative factors of schizophrenia, through a qualitative descriptive case study method. The researcher is a single case study type involving one schizophrenia survival participant. The assessment procedure was carried out using semi-structured interviews, descriptive observation, and graphical psychological tests, SSCT, MMSE and CPM. The research findings state that schizophrenia occurs due to multiple factors, namely patterns of biopsychosocial interaction and demographic characteristics. Biological factors include a genetic history in the family of schizophrenia or mental health problems, a history of using alcohol and tobacco. Psychological factors in the form of self-characteristics that lack resilience in dealing with problems and stress coping strategies that are relatively mal-adaptive. Social factors include a history of conflict and less positive social relations, both with the primary environment such as: parents, siblings, wife and children and the secondary environment such as neighbors, co-workers, and friends. Demographic factors in the form of economic problems and low education, in the form of economic demands from the wife and parents-in-law, as well as a history of not completing high school education equivalent.Skizofrenia sebagai masalah psikosis dengan jumlah pengidap di Indonesia menyentuh angka 2 juta jiwa, banyaknya kasus tidak sebanding dengan pengetahuan masyarakat terkait faktor penyebab skizofrenia. Tujuan penelitian menyajikan gambaran deskriptif faktor penyebab skizofrenia, melalui metode kualitatif studi kasus deskriptif. Peneliti berjenis single case study dengan melibatkan satu partisipan survival skizofrenia. Prosedur asesmen dilakukan dengan wawancara semi terstruktur, observasi deskriptif dan psikotes grafis, SSCT, MMSE dan CPM. Temuan penelitian menyebutkan skizofrenia terjadi karena multi faktor yaitu pola interaksi biopsikososial dan karakteristik demografi. Faktor biologis meliputi terdapat riwayat genetik dalam keluarga yang mengalami skizofrenia ataupun masalah kesehatan mental, riwayat penggunaan zat alkohol dan tembakau. Faktor psikologis berupa karakteristik diri yang kurang resiliensi dalam menghadapi permasalahan serta strategi coping stress yang relatif mal adaptif. Faktor sosial berupa adanya riwayat konflik dan relasi sosial yang kurang positif, baik dengan lingkungan primer seperti: orang tua, saudara, istri dan anak dan lingkungan sekunder seperti tetangga, rekan kerja dan teman. Faktor demografi berupa masalah ekonomi dan pendidikan rendah, berupa tuntutan ekonomi dari pihak istri dan mertua, serta riwayat tidak menyelesaikan pendidikan SLTA sederajat.